The Influence of Green Marketing Towards Buying Interest Products (Study at MSMEs Kiwari Bamboe) - Widiyana Nurulita, Vica; Nurfitriya, Mira; Rachmani, Nizza Nadya (A Social Science and Entrepreneurship Journal, 2022)
The purpose of this study is to decide the impact of green marketing towards buying interest products in Kiwari Bamboe MSMEs. The object of this examination is Kiwari Bamboe Micro, Small and Medium Enterprises in Cintaraja, Tasikmalaya Regency. This study uses two variables to test the effect, namely the independent variable in this study is green marketing (X) and the dependent variable is buying interest (Y). This research was conducted using a survey method with a quantitative approach. The results of this study are that green marketing has a positive effect on product buying interest in Kiwari Bamboe MSMEs.